An Analysis of Punctuation of Direct and Indirect Speech in the Writing of First- Grade Students at SMK Maospati, Magetan (Eduscotech, 2024)
This study examines the accuracy of punctuation in direct and indirect speech in the English writing of first-grade students at SMK Maospati, Magetan. Using a descriptive qualitative approach supported by error analysis, the research identifies common types of punctuation errors, evaluates students’ accuracy levels, and explores contributing factors to these mistakes. Data were collected from students’ written assignments, classroom observations, and interviews with teachers, complemented by library research to strengthen linguistic analysis. The findings indicate that students frequently make errors in punctuating direct speech, particularly in the placement of quotation marks, commas, capitalization, and sentence-ending punctuation. In indirect speech, students often misuse or overuse quotation marks, incorrectly place commas, and produce hybrid structures that blend direct and indirect conventions. Overall accuracy levels were low and inconsistent, especially when students encountered complex sentence forms. Factors contributing to these errors included L1 interference, limited explicit instruction, insufficient exposure to accurate English texts, inadequate corrective feedback, and cognitive overload during writing tasks. The study concludes that explicit and systematic instruction on punctuation supported by contextualized examples and guided practice is essential for improving students’ writing accuracy. Recommendations include strengthening classroom instruction, increasing reading exposure, and developing pedagogical materials that emphasize punctuation in reported speech.